Green tea moisturizer improves skin hydration in elderly - Tjandra, Oentarini; Wijayadi, Linda J; Rumawas, Marcella E (Universa Medicina, 2018)
BACKGROUNDDry skin is a major skin health problem in elderly. Green tea, which has an antioxidant effect, has recently been used as an active ingredient in moisturizing creams; yet the effect has not been well studied. This study compares the skin hydration effect of green tea and vitamin E moisturizer among elderly.METHODSThis quasi-experimental study involved 60 elderly living in Tresna Werda Budi Mulia 4 Social Institution, Jakarta. Using the Runve HL 611 skin analyzer, skin capacitance was measured prior to experiment and every following week during the 5-week application of green tea and vitamin E skin moisturizer on both forearms. The consecutive measurement data was analyzed using Generalized Estimating Equation to compare the relative changes in skin hydration between the two moisturizer groups over 5 weeks of intervention. RESULTSThe green tea moisturizer showed more significant increases in skin hydration level than the vitamin E moisturizer at all measurement sites on right arm and proximal left arm (p= 0.021), and medial and distal left arm (p= 0.034). Skin hydration levels significantly changed over time at proximal (p=0.021), medial (p=0.006) and distal (p=0.006) right arm, and medial left arm (p=0.021). A parallel trend of skin hydration improvements for both moisturizer groups indicated no correlation between the moisturizer type and the duration of usage (p >0.05) in all measurement locations. No side effects were observed during application period in both groups.CONCLUSIONRoutine use of moisturizer containing green tea may improve skin hydration in elderly.